Determinants of FDI establishment mode choice of Polish firms. The OLI paradigm perspective - Gorynia, Marian; Nowak, Jan; Trąpczyński, Piotr; Wolniak, Radosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
This study attempts to investigate the establishment mode choice of Polish firms when entering foreign markets via foreign direct investment (FDI) in the light of John Dunning’s eclectic OLI model. A dichotomous mode choice between greenfield investment and acquisitions forms the basic framework for analysis. The theoretical part contains the application of Dunning’s model to the investigated relationships with the said establishment mode choice as well as an overview of the empirical research conducted so far on outward foreign direct investment (OFDI) from the countries of Central and Eastern Europe (CEE). Seven research hypotheses are formulated in this context and tested on a sample of firms registered in Poland with ongoing FDI. Data collection was made using an online survey, then four models were used to test the statistical significance of the hypothesized relationships. The results showed no statistical significance for the hypotheses linking mode choice with ownership and internalization advantages. Positive verification was recorded for all the identified location advantages. Thus Dunning's OLI framework demonstrates the limited applicability to the establishment mode choices in an advanced emerging country context. The study concludes with an outline of its contribution to OFDI research, its limitations and finally with recommendations for future research in this area
Argumenta Oeconomica, 2016, Nr 2 (37), s. 67-92
Keywords: foreign expansion; foreign direct investment; establishment mode choice; greenfield vs. acquisitions; OLI paradigm; Poland